Answer:
Step-by-step explanation:
We have been given that n=-2 verified as a solution to the equation .
As n=-2 is the solution for our given equation, so it will satisfy our equation.
Let us substitute n=-2 is our given equation.
Since the value of n satisfies our equation, therefore, last line of the justification will be .
By the inequality for x over on the right side if x is equal to or greater than 2 you use the bottom equation.
G(2) means x is 2.
Using the bottom equation replace the x’s with 2 and solve.
X^3 -9x^2 +27x-25
2^3 -9(2)^2+27(2)-25
Simplify:
8 -36 + 54-25 =1
The answer is A. 1
Answer:
666.67π .ft^3
<em>here's</em><em> your</em><em> solution</em>
<em>=</em><em>></em><em> </em><em>radius</em><em> of</em><em> </em><em>cone </em><em>=</em><em> </em><em>1</em><em>0</em><em> </em><em>ft</em>
<em>=</em><em>></em><em> </em><em>height</em><em> of</em><em> </em><em>cone </em><em>=</em><em> </em><em>2</em><em>0</em><em> </em><em>ft</em>
<em>=</em><em>></em><em> </em><em>volume</em><em> of</em><em> </em><em>cone </em><em>=</em><em> </em><em>πr^</em><em>2</em><em>h</em><em>/</em><em>3</em>
<em>=</em><em>></em><em> </em><em>putting</em><em> the</em><em> value</em><em> of</em><em> </em><em>radius</em><em> and</em><em> height</em><em> </em>
<em>=</em><em>></em><em> </em><em> </em><em> </em><em>volume</em><em> </em><em>=</em><em> </em><em>1</em><em>0</em><em>^</em><em>2</em><em>*</em><em>2</em><em>0</em><em>/</em><em>3</em><em>π</em>
<em>=</em><em>></em><em> </em><em>volume</em><em> </em><em>=</em><em> </em><em>6</em><em>6</em><em>6</em><em>.</em><em>6</em><em>7</em><em>π</em><em> </em><em>.</em><em>ft^</em><em>3</em>
<em>hope</em><em> it</em><em> helps</em>
Answer:
y=3x+4
Step-by-step explanation:
y-y1=m(x-x1)
y-4=3(x-0)
y-4=3x
y=3x+4